Mexican entrepreneurship: a comparison of self-employment in Mexico and the United States - Robert W. Fairlie; Christopher Woodruff (Institute for the Study of Labor (IZA), 2006)
Nearly a quarter of Mexico's workforce is self employed. In the United States, however, rates of self employment among Mexican Americans are only 6 percent, about half the rate among non-Latino whites. Using data from the Mexican and U.S. population census, we show that neither industrial composition nor differences in the age and education of Mexican born populations residing in Mexico and the U.S. accounts for the differences in the self employment rates in the two countries. Within the United States, however, estimates indicate that low levels of education and the youth of Mexican immigrants residing in the United States account for roughly half of the Mexican immigrant/U.S. total difference in self-employment rates for men and the entire difference for women. We also find some suggestive evidence that for both men and women, Mexican immigrant self-employment rates may be higher for those who reside in the United States legally and are fluent in English, and for men, those who live in ethnic enclaves.
Keywords: J15; J23; 330; entrepreneurship; self-employment; Mexico; Mexican-Americans; Mexikaner; Unternehmer; Selbstständige; Vergleich; USA; Mexiko